The Role Of Ship Crew Agency In Improving Ship Crew Performance At PT. Topaz Maritime - Awel Suryadi; Fitri Zuhriyah; Izzuddin Akbar Satria (Politeknik bumi Akpelni, 2025)
Crew agency has an important role to play in improving crew performance through the supervision of crew responsibilities. If there is a decrease in performance by the crew while working, this has a negative impact on the company, so that crew performance problems must be handled properly by the crew agency. this study aims to identify the obstacles, impacts, and efforts made by the crew agency of PT. Topaz Maritime in improving crew performance. This research uses a qualitative descriptive method. Data collection techniques include interviews, observation, and documentation, then the data is analysed with qualitative analysis. The results showed that the obstacles faced by the crew agency in improving crew performance at PT Topaz Maritime are the lack of adequate supervision and the crew's low awareness of performance. The impact of declining crew performance includes disruption to operational hours, decreased work quality and efficiency, and work accidents. Efforts made by the crew agency include providing crew training and motivation, conducting pre-joining briefings before joining the ship, giving appreciation to the crew, and effective supervision of shipboard rules and procedures.